PENDAMPINGAN PROGRAM PENGENDALIAN INFLASI DAERAH PADA KLASTER CABAI MERAH - Ida Marina; Sri Ayu Andayani; Dinar; umar Dani; Kosasih Sumantri (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Inflationary pressure in West Java province in January to March 2021 (quarter 1) was lower than October to December 2020 (quarter IV), the lower inflation rate was caused by limited demand due to the implementation of Restrictions on the activities of the Javanese Community West (PPKM) and controlling the supply of food commodities because the harvest has just begun for several food commodities, including red chili. Red chilies experienced an increase in prices due to the La Nina weather factor so that farmers failed to harvest and limited supplies. In an effort to maintain price affordability and supply availability to mitigate existing risks. Assistance is provided to the red chili cluster in the Mekar Mulya farmer group with the aim of supporting the TPID program with a 4K framework (Price Affordability, Supply Availability, Smooth Distribution, and Effective Communication)